1983
DOI: 10.1007/bf01059061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential causes for the incomplete bioavailability of furosemide: Gastric first-pass metabolism

Abstract: Potential causes for reported incomplete (usually 40-60%) and often highly variable (e.g., 11-79%) bioavailability of furosemide in humans were investigated. The drug was found to be fairly stable in gastric fluids and its hepatic first-pass elimination (HFPE) was estimated to be much less than 6% based on published i.v. data. The rat was used as the main model for extensive evaluation. About 4% (n = 4) of dose was recovered unchanged in the GI tract after i.v. injection while about 40% (n = 12) was recovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 172 publications
(133 citation statements)
references
References 32 publications
4
127
2
Order By: Relevance
“…administration of CZX were unconjugated CZX (not CZX glucuronides) and conjugated OH-CZX, respectively. The percentage of hepatic extraction ratio (hepatic firstpass effect) was roughly estimated by dividing the nonrenal clearance (as mentioned earlier, the CL of CZX in Table 3 could represent the metabolic clearance of CZX) by the reported hepatic plasma flow in rats assuming that nonrenal clearance of CZX was attributed solely to the liver (hence the percentage represents maximal possible value) (Lee and Chiou, 1983). The hepatic plasma flow in rats was estimated based on the reported hepatic blood flow of 30.4 ml/ min/kg (Davies and Morris, 1993) and hematocrit of approximately 45% (Mitruka and Rawnsley, 1981) in rats.…”
Section: Discussionmentioning
confidence: 99%
“…administration of CZX were unconjugated CZX (not CZX glucuronides) and conjugated OH-CZX, respectively. The percentage of hepatic extraction ratio (hepatic firstpass effect) was roughly estimated by dividing the nonrenal clearance (as mentioned earlier, the CL of CZX in Table 3 could represent the metabolic clearance of CZX) by the reported hepatic plasma flow in rats assuming that nonrenal clearance of CZX was attributed solely to the liver (hence the percentage represents maximal possible value) (Lee and Chiou, 1983). The hepatic plasma flow in rats was estimated based on the reported hepatic blood flow of 30.4 ml/ min/kg (Davies and Morris, 1993) and hematocrit of approximately 45% (Mitruka and Rawnsley, 1981) in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics and/or pharmacodynamics of furosemide, a loop diuretic, in humans [6][7][8] and animals [9][10][11][12][13][14] have been extensively studied, however, the effects of diabetes mellitus on the pharmacokinetics and pharmacodynamics of furosemide seemed not to be thoroughly studied. Pharmacokinetic and pharmacodynamic changes of azosemide, another loop diuretic, after its intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it could be expected that, compared with control rats, the CL NR of theophylline would be slower in 24-h KPLPS rats, because theophylline is a low hepatic extraction ratio drug in rats. The hepatic first-pass effect of theophylline in this study was estimated using a reported equation (Lee and Chiou, 1983) based on the CL NR of …”
Section: Resultsmentioning
confidence: 99%